Gluteal Necrosis and Lumbosacral Plexopathy in a Diabetic Patient after Renal Transplantation - M. A. Asgari; N. Masoumi; H. Argani (Case Reports in Urology)
A 34-year-old diabetic patient underwent a renal transplant which was complicated by right side lower extremity paresis and numbness with gluteal necrosis. The main reason was ligation of internal iliac artery of the same side as a result of extensive microvascular obstruction due to severe atheromatous plaque. This is a rare complication which is mostly reported in aneurysmal patients after bypass surgery. The gluteal necrosis is a serious complication which, as in our patient, resulted in patient’s death in most of the reported cases. Because of catastrophic nature of this condition, identifying preventive measures is extremely important.